PENGARUH KINERJA PETUGAS TERMINAL INSPECTION SERVICE (TIS) DALAM PENGAWASAN FASILITAS TERMINAL TERHADAP KEPUASAN PENUMPANG BANDAR UDARA BANYUWANGI - Azizah, Nadhifah Nur; Fauziah, Syifa (Jurnal Ground Handling, 2024)
The progress of Angkasa Pura II shows the rapid use and improvement of the airport service business through the addition of various infrastructure improvements and facilities at the airports managed by the company. In addition to providing the facilities needed by its passengers at the airport but also improving the performance of its officers. PT Angkasa Pura has a unit responsible for overseeing facilities at the airport, namely the Terminal Inspection Service (TIS) unit which is authorized to monitor and ensure the smooth operation of airport terminal facilities. The research method was carried out by distributing questionnaires to passengers as subjects. This research is quantitative in nature using purposive sampling technique in distributing questionnaires. Data analysis was carried out by simple linear regression as well as descriptive analysis. For data processing, researchers used SPSS version 27 software. Based on the research results, the regression coefficient value of the Performance variable is 0.631. This indicates that there is a positive influence between performance and passenger satisfaction. In other words, the higher the performance, the higher the level of passenger satisfaction that can be achieved. The t value is 7.921 with a significant value of 0.000 <0.05. For the coefficient of determination, it was found that the TIS Officer Performance variable had an influence of 39% on the Passenger Satisfaction variable. The results of the descriptive analysis of the performance of TIS officers have an average that shows a high score classification, which means that passenger satisfaction has reached a good standard suitability for supervision of terminal facilities at Banyuwangi International Airport.